Elaboración de cerveza artesanal con pulpa de naranjilla (solanum quitoense lam.) y maracuyá (pasiflora edulis). - Guerrero Sumba, Freddy Alexis (2022)
CRAFT BEERS ARE A RESULT FROM THE WHOLE PRODUCT MIXING FERMENTATION OF SUGARS FROM BARLEY MALTS, it is however harmful to health, the abuse of this alcoholic drink in an excessive and prolonged consumption, the present research aims to recommend as an alternative consumption the addition of naranjilla pulp (Solanum quitoense Lam. ) and passion fruit (Pasiflora edulis) in the craft beer American IPA, where four treatments were designed (T1: 50% naranjilla pulp, 50% passion fruit pulp; T2: 37.5% naranjilla pulp, 62.5% passion fruit pulp; T3: 25% naranjilla pulp, 75% passion fruit pulp; T4: 75% naranjilla pulp, 25% passion fruit pulp. ), the results of the physical chemical and microbiological analyses, 48 days after processing allowed to know that there is no significant difference and that these are within the maximum and minimum levels of the standard (INEN, 2013) between treatments, within the sensory test was applied to 9 people, showing them that treatment 3 (T3: 25% naranjilla pulp, 75% passion fruit pulp) these ingredients are ideal for consumption, in this study, the treatment with the greatest difference with respect to beer characteristics, color, aroma, flavor, bitterness, freshness, those are the safe and quality standards for beer. Keywords: Pulp, beer, naranjilla, passion fruit, characteristics.